A probability problem by Santiago Hincapie

n = 1 F n x n = x 505 \large{ \sum _{ n=1 }^{ \infty }{ \frac { F_{ n } }{ { x }^{ n } } =\frac { x }{ 505 } } }

Find the value of x , x > 0 x, \ x > 0 such that the above equation satisfies where F n F_n denotes the n th n^{\text{th}} Fibonacci number .


The answer is 23.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Tom Van Lier
Nov 11, 2015

Using the following property :

n = 1 F n x n = x x 2 x 1 , \sum\limits_{n=1}^\infty \dfrac{F_{n}}{x^n} = \dfrac{x}{x^2 - x - 1} ,

we deduce that x 2 x 1 = 505 x^2 - x - 1 = 505 , which gives us the answers -22 and 23.

23 \Rightarrow 23 is the only positive x.

Can you proof this property?

Santiago Hincapie - 5 years, 7 months ago

Log in to reply

Let S = n = 1 F n x n \displaystyle S = \sum_{n=1}^\infty \frac{F_n}{x^n} . F 1 = F 2 = 1 F_1 = F_2 = 1 and F n = F n 1 + F n 2 F_n = F_{n-1} + F_{n-2} so

S = n = 1 F n x n = 1 x + 1 x 2 + n = 3 F n x n = 1 x + 1 x 2 + n = 3 F n 1 + F n 2 x n = 1 x + 1 x 2 + n = 3 F n 1 x n + n = 3 F n 2 x n = 1 x + 1 x 2 + 1 x n = 2 F n x n + 1 x 2 n = 1 F n x n = 1 x + [ 1 x + 1 x 2 ] n = 1 F n x n = 1 x + [ 1 x + 1 x 2 ] S \begin{aligned} S &= \sum_{n=1}^\infty \frac{F_n}{x^n} \\ &= \frac{1}{x} + \frac{1}{x^2} + \sum_{n=3}^\infty \frac{F_n}{x^n} \\ &= \frac{1}{x} + \frac{1}{x^2} + \sum_{n=3}^\infty \frac{F_{n-1}+F_{n-2}}{x^n} \\ &= \frac{1}{x} + \frac{1}{x^2} + \sum_{n=3}^\infty \frac{F_{n-1}}{x^n} + \sum_{n=3}^\infty \frac{F_{n-2}}{x^n} \\ &= \frac{1}{x} + \frac{1}{x^2} + \frac{1}{x} \sum_{n=2}^\infty \frac{F_n}{x^n} + \frac{1}{x^2} \sum_{n=1}^\infty \frac{F_n}{x^n} \\ &= \frac{1}{x} + \left[ \frac{1}{x} + \frac{1}{x^2} \right] \sum_{n=1}^\infty \frac{F_n}{x^n} \\ &= \frac{1}{x} + \left[ \frac{1}{x} + \frac{1}{x^2} \right] S \end{aligned}

Thus, S = x x 2 x 1 S = \dfrac{x}{x^2-x-1} .

Jake Lai - 5 years, 6 months ago

Log in to reply

Turns out f ( x ) = x x 2 x 1 = f ( 1 x ) f(x)=\frac{x}{x^2-x-1}=f(\frac{1}{x})

Julian Poon - 5 years, 6 months ago

Thanks for writing that out, I didn't have time for it.

Tom Van Lier - 5 years, 6 months ago

did it the same way!

Divyansh Choudhary - 5 years, 5 months ago

Apply this .

Pi Han Goh - 5 years, 6 months ago
Otto Bretscher
Sep 29, 2015

I believe there is a second answer besides 23, namely, x = 22 x=-22

Thank you. The problem statement has been edited.

Brilliant Mathematics Staff - 5 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...